Single-cell multiomics of neuron activation reveals context-specific genetics of brain disorders - Lifan Liang; Siwei Zhang; Zicheng Wang; Hanwen Zhang; Chuxuan Li; Christina Thapa; Emily K. Oh; David Sirkin; Xiaotong Sun; Alexandra Barishman; Ada McCarroll; Alexandra C. Duhe; et al. (Science, 2026)
Most causal variants for neuropsychiatric disorders (NPD) remain unknown. A major hurdle is that disease variants may act in specific contexts, such as during neuronal activation, which is difficult to study in vivo at the population level. We profiled single-nucleus neuron-activation multiomics in human induced pluripotent stem cell–derived neurons from 100 donors, revealing the NPD-relevant transcriptomic and epigenomic landscape of neuronal activation. We identified abundant genetic variants associated with activity-dependent gene expression and chromatin accessibility, the latter explaining larger proportions of NPD heritability. Integrating multiomics data with genome-wide association studies further revealed NPD risk variants and genes with effects detected only upon stimulation, such as activity-dependent cholesterol metabolism. Our work highlights the power of cell stimulation to reveal context-specific “hidden” genetic effects.